An Investigation into Current Sustainable Management Whale Watching Strategies Comparing New England and the Pacific Northwest Regions of the United States - Golini, Olivia (2022)
The advantages and disadvantages of whale watching have been highly researched in previous studies, however there is an absence of literature regarding guideline compliancy and efficacy. Thus, this paper aims to explore the current management strategies being utilized by tourism operators in New England and the Pacific Northwest through qualitative interviews and thematic analysis. Findings show that no significant regional differences were found between the study sites. Nine themes were discovered; Encouraging conservation efforts, Education, Dissatisfaction with current management, and High community and stakeholder involvement are among the most prominent. Urgent changes in management strategies are essential to the long-term sustainability of the industry. It is proposed that the creation of whale watch associations is beneficial to sustainability and whale watching vessels be regarded as an enforcement agency.